Re-imagining money to broaden the future of development finance: What Kenyan community currencies reveal is possible for financing development - Jem Bendell; Matthew Slater; William Ruddick (United Nations Research Institute for Social Development (UNRISD), 2015)
This paper argues that it is important to understand the nature of money and its impacts to be able to engage better with currency innovations for sustainable development. The paper focuses on the case of Bangla-Pesa, an alternative currency used in poor urban areas in Kenya, to demonstrate how currency innovation can work for poor people. The Kenyan non-governmental organization, Grassroots Economics, is helping to create business networks in the poorest urban areas. Vouchers, issued and honoured by every member of the network, function as a form of currency. This has led to an increase in turnover of more than 20 percent and corresponding economic growth, as well as a reduction of waste and unemployment. This model requires very little investment. However, despite an excellent and documented track record, Grassroots Economics was unable to secure any institutional funding. The authors suspect that this lack of support arises from a lack of understanding among development professionals about the nature of money, how new currencies can be created and which innovations are useful. This paper therefore seeks to inform policy makers about the nature of money, offering a new typology of money called the Value-Sequence Typology, which categorizes "monies" based on the process and justification for issuing new units, or in this case, vouchers. The authors propose a new definition of money as a system of agreements and symbols which influence the creation and exchange of value and power. The agreements, whether explicit or implicit, about the relationship between the symbols of money and when the actual value of what was monetized changes hands, (before, during, or after) are the most important signifier of money types. Grassroots economics, in a context of a community of micro-entrepreneurs, uses a Collaborative Credit System (CCS) in which members issue interest free credit to each other. This is similar to how most national currencies are created, yet it is done peer-to-peer, without the involvement of banks. The authors feel this is particularly important in a time of declining official development assistance. Creative insight into the nature of money could enable a new era in development cooperation through promotion of collaborative credit systems.
Keywords: 330